Globalization, Wages, and the Quality of Jobs : Five Country Studies - Robertson, Raymond; Brown, Drusilla; Pierre, Gaëlle; Sanchez-Puerta, María Laura (World Bank, 2012)
The country studies in this volume analyze the link between globalization and working conditions in Cambodia, El Salvador, Honduras, Indonesia, and Madagascar. These countries vary significantly in population, economic circumstances, region, history, and institutions. All have experienced liberalization and globalization in the last 20 years. The heterogeneity of these countries provides the basis for a useful comparison of the effects of globalization on working conditions. As suggested in the framework, each country study has three main components: a description of the country's experience with globalization, a qualitative part that analyzes country-specific aspects of working conditions, and an analysis of changes in interindustry wage differentials (IIWDs) that can be compared across countries. In general, globalization has been characterized by export-driven foreign direct investment (FDI) concentrated in relatively few sectors. Export-driven FDI in the apparel sector plays a prominent role in each country, although to varying degrees. In Cambodia, apparel made up 82 percent of all merchandise exports in 2003. Nearly two-thirds of that total was destined for the U.S. market. Virtually all factories in the Cambodian garment sector are foreign owned. Honduras rose from being the 34th largest supplier of apparel to the United states (U.S.) market in 1990 to fourth place in 2003. In 2003, two-thirds of all Honduran exports to the U.S. were garments and more than 82 percent of all Honduran workers worked in foreign-owned factories. A similar pattern emerges for El Salvador. For Madagascar, apparel exports from the Zone Franche were the primary force behind the country's remarkable export growth and its transition from exporting primary products to exporting manufactured products between 1990 and 2005. By 2001, Madagascar had become the second most important clothing exporter in Sub-Saharan Africa as measured by total export value.